Smoke-free adolescents: effectiveness of an educational intervention : Controlled, before and after study - Gulayin, Pablo Elías (2018)
Smoking is considered the main cause of preventable death worldwide. Most smokers start using tobacco at an early age, especially during adolescence. The objective of this study was to identify the determinants of adolescent use of tobacco and assess the impact of an educational intervention on the prevalence of smoking. Methods. Controlled, before and after study conducted between 2010 and 2012 at two secondary schools in the city of La Plata. A baseline survey was administered at both schools followed by two subsequent measurements; an educational intervention aimed at youth aged 12 and 13 years was implemented in one of the schools. Multiple regression models were used to identify the outcome measures associated with smoking and assess the impact of the intervention. Results. A total of 1911 surveys were included (school A: 617; school B: 1294). The outcome measures associated with adolescent smoking were having a sibling who smokes (odds ratio [OR]: 2.55), a mother who smokes (OR: 2.32), age (OR: 1.92), and female sex (OR: 1.75). The OR adjusted for these determinants to be a current smoker at the intervention school versus the control school was 0.54 (95% confidence interval [CI]: 0.35-0.83) in the first year of follow-up and 0.98 (95% CI: 0.60-1.61) in the second year. Conclusions. Having a mother or a sibling who smokes, age, and female sex were strongly correlated to cigarette smoking. The educational intervention had a positive effect in the first year of follow-up, which was not maintained over time.